Efficacy and safety of ropivacaine and lidocaine in patients undergoing peribulbar anaesthesia for small incision cataract surgery - Rekha Mudhol; Bhagyajyothi B. K; Tanmay Gupta (Al Ameen Medical College, 2020)
Background: Ropivacaine is found to be a suitable choice for local anaesthesia showing a short and predictable onset of surgical anaesthesia with better control of post-operative pain relief. Objectives: To compare the intra-operative clinical properties of 0.75% Ropivacaine and 2 % Lidocaine for small incision cataract surgery. Methods: Patients (n=64) undergoing cataract surgery with Posterior Chamber Intraocular Lens (PCIOL) implantation, were randomized into two groups i.e Ropivacaine group and Lidocaine group to receive peribulbar injection. Antibiotic drops were instilled in the patient's eyes a day prior to the surgery and dilating eye drops were instilled in the eye to be operated on the day of the surgery. The test dose was given to check the sensitivity followed by procedure involved for peribulbar anaesthesia. Results: The mean time of onset of analgesia for Lidocaine group is 118.13±60.93 seconds whereas for Ropivacaine group is 60.94±36.93 seconds. The mean time of onset of akinesia for Lidocaine group is 237.19±87.67 seconds whereas for Ropivacaine group is 183.75±89.76 seconds .The median of analgesia (p<0.0001) and akinesia (p=0.0294) was significantly higher for Lidocaine group than Ropivacaine group. Conclusion: 0.75% Ropivacaine has better analgesic and akinesia effect than Lidocaine group for small incision cataract surgeries.